Diagnosis of occupational rhinitis to dust and gasses using peak nasal inspiratory flow - Deasi Anggraini; Retno Sulistyo Wardani; Nina Irawati; Muchtarudin Mansyur; Rahajoe Dharmaningsih; De-Yun Wang (Oto Rhino Laryngologica Indonesiana, 2014)
Background: The recent development in technology and industry has increased the incidence of occupational disorders of which eventually affect the productivity and cost of related industries. Whether the products or the waste-materials are harmful to airway function, it needs to be investigated. Purpose: To study the incidence of occupational \rhinitis (OR) caused by exposure of sodium lauryl sulfate dust and irritant gases in the workplace. Methods: In this prospective study, 115 industrial workers who were exposed daily to multi–irritant material were investigated with questionnaire, anterior rhinoscopy, nasal endoscopy, peak nasal inspiratory flow (PNIF) meter, skin prick test, and nasal mucous scrapping before (V1) and after 8 hours (V2) work. The diagnosis of OR was made when symptoms of rhinitis worsened on workdays and a decrease of PNIF (≥20%) at V2. In addition, hours of daily exposure to irritant, years of working, improper usage of personal protection device (nasal and oral mask), and smoking were assessed by bivariate and multivariate analysis. Result: 32 workers of 115 (27.8%) were diagnosed as OR based on increased rhinitis symptoms during workdays and decreased PNIF after work. Incidence of OR increased in workers who had worked >10 years=2.15 (IC 95%:1.19-3.87, p=0.009) and who did not use personal protective equipment properly (p=0.04, RR:2.3, IC 95%:1.29-4.28). Conclusion: Exposure to occupational reagent such as sodium lauryl sulfate dust and multi-irritant gasses was a causal factor of OR. A proper perusal of personal protection equipment (PPE) is mandatory in workplace to minimize the risk of developing OR. Keywords: Occupational rhinitis, nature exposure of occupational agents, peak nasal inspiratory flow,nasal obstruction, personal protection equipment. ABSTRAKLatar belakang: Kemajuan teknologi dan industri akhir-akhir ini, meningkatkan pemaparan saluran napas terhadap produk atau sisa industri yang merupakan zat iritan. Sebagai akibatnya, insidens kelainan akibat kerja semakin meningkat, yang dapat mempengaruhi produktivitas dan peningkatan beban biaya industri. Seberapa besar pengaruhnya terhadap fungsi saluran napas, hal ini masih perlu diteliti lebih lanjut. Tujuan: Penelitian dilakukan untuk mengetahui insidens Rinitis Akibat Kerja (RAK) yang diakibatkan pajanan debu sodium lauryl sulfate dan gas iritan di tempat kerja. Metode: Pada studi prospektif ini, 115 pekerja yang terpajan setiap hari dengan material multi-iritan diteliti berdasarkan kuesioner, pemeriksan rinoskopi anterior, nasoendoskopi, Peak Nasal Inspiratory Flow (PNIF) meter, uji cukit kulit dan kerokan mukosa hidung sebelum (V1) dan sesudah 8 jam (V2) bekerja. Diagnosis RAK ditegakkan jika didapati perburukan gejala hidung disertai dengan penurunan (>20%) hasil PNIF pada V2. Sebagai tambahan, waktu pajanan iritan (jam), masa kerja (tahun), penggunaan alat perlindungan diri (APD) seperti masker hidung dan mulut secara kurang benar, serta kebiasaan merokok dianalisis dengan analisis bivariat dan multivariat (model regresi logistik). Hasil: 32 dari 115 pekerja (27,8%) didiagnosis sebagai RAK berdasarkan perburukan gejala hidung selama bekerja dan penurunan PNIF sesudah bekerja. Insidens RAK meningkat pada pekerja yang telah bekerja lebih dari 10 tahun=2.15 (95% IK:1,19–3,87, p=0,009) dan para pekerja yang tidak menggunakan APD (masker hidung dan mulut) secara benar, yaitu (p=0,04, RR: 2.4, 95% IK:1,29–2,48). Kesimpulan: Pajanan bahan kimia seperti debu sodium lauryl sulfate dan berbagai gas iritan merupakan faktor penyebab RAK. Penggunaan APD secara benar adalah mutlak untuk menurunkan risiko terjadinya RAK. Kata kunci: Rinitis akibat kerja, pajanan alamiah bahan berbahaya di tempat kerja, peak nasal inspiratory flow, hidung tersumbat, alat pelindung diri